Association of nociplastic and neuropathic pain components with the presence of residual symptoms in patients with axial spondyloarthritis receiving biological disease-modifying antirheumatic drugs - Joachim Sieper; Denis Poddubnyy; Hildrun Haibel; Fabian Proft; Mikhail Protopopov; Valeria Rios Rodriguez; Murat Torgutalp; Judith Rademacher; Henriette Käding; Fares Al Mohamad (RMD Open)
Objective To evaluate the association of nociplastic (NoP) and neuropathic pain (NP) components with residual symptoms in patients with radiographic axial spondyloarthritis (r-axSpA) receiving biological disease-modifying antirheumatic drugs (bDMARDs).Methods 78 patients with r-axSpA from the GErman SPondyloarthritis Inception Cohort receiving a bDMARD for at least 3 months were included in this analysis. The Widespread Pain Index (WPI) and the PainDETECT (PD) questionnaire were used to quantify the NoP and the NP components, respectively. Axial Spondyloarthritis Disease Activity Score (ASDAS) and the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) were used as measures of residual symptoms. C reactive protein (CRP) was used as a measure of systemic inflammatory activity. Univariable and multivariable regression analyses of disease activity were performed. The regions of the WPI score and items of the PD score were used for cluster analyses.Results Linear multivariable regression analysis showed that WPI and PD were independently associated with ASDAS (b=0.1, 95% CI 0.04 to 0.17, and b=0.05, 95% CI 0.02 to 0.08, respectively) and BASDAI (b=0.24, 95% CI 0.08 to 0.39, and b=0.17, 95% CI 0.1 to 0.25, respectively) in r-axSpA patients receiving stable treatment with bDMARDs. Furthermore, WPI and PD were found to be significantly associated with the presence of relevant residual symptoms as defined by BASDAI ≥4 (OR 1.93, 95% CI 1.09 to 4.15, and OR 1.32, 95% CI 1.04 to 1.85, respectively). The effects were present also in patients with normal level of CRP. Cluster analysis revealed three distinct pain distribution profiles and four specific sensory symptom constellations allowing differentiation of different pain subtypes.Conclusion Both NoP and NP components seem to be associated with residual symptoms in patients with r-axSpA receiving treatment with bDMARDs.